2021
DOI: 10.1021/acs.jchemed.1c00122
|View full text |Cite
|
Sign up to set email alerts
|

Finding the pKa Values of a Double-Range Indicator Thymol Blue in a Remote Learning Activity

Abstract: Colorful transitions of various acid−base indicators have been used to illustrate the concept of chemical equilibria, especially in spectrophotometric determination of the equilibrium constants or pK a values. To accommodate an online laboratory environment necessitated by the COVID-19 pandemic, this work employs color analyses from digital images to determine the pK a values of a double-range indicator thymol blue. The experiment has been developed into an online activity to teach chemical equilibria and diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The agreement between the experimental and theoretical diagrams can also be improved by using more robust mathematical multicomponent analysis to determine the concentration of each species. , The advantage of the methodology described above is in its simplicity and accessibility for students regardless of their mathematical background. A natural extension of this experiment is to calculate the p K a ’s using the measured absorbances and the equations reported previously for monoprotic systems. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement between the experimental and theoretical diagrams can also be improved by using more robust mathematical multicomponent analysis to determine the concentration of each species. , The advantage of the methodology described above is in its simplicity and accessibility for students regardless of their mathematical background. A natural extension of this experiment is to calculate the p K a ’s using the measured absorbances and the equations reported previously for monoprotic systems. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…A natural extension of this experiment is to calculate the pK a 's using the measured absorbances and the equations reported previously for monoprotic systems. 17,25,26 Students used their experimental results to determine that H 2 A is the thymol blue predominant species when pH < pK a1 , HA − is when pK a1 < pH < pK a2 , and A 2− is the major species when pK a2 < pH.…”
Section: Construction Of Speciation Diagramsmentioning
confidence: 99%
“…In 2020, Kovarik et al reviewed laboratory experiments carried out using digital images obtained using smartphones, desktop scanners, and webcams. Since then, several new laboratory experiments involving digital images have been published. …”
Section: Introductionmentioning
confidence: 99%
“…6 Several laboratory practices describing quantitative colorimetry using electronic instruments were published in this Journal. These publications were reviewed by Kovarik et al, 7 and, since that, some laboratory experiments have been published such as starch quantification in ripe banana, 8 determination of biodiesel in diesel blends, 9 analysis of salivary amylase using starch from food as a substrate, 10 iron(III) determination in water, 11,12 quantification of colored household products, 13 determination of ciprofloxacin, 14 and acetylsalicylic acid in pharmaceuticals, 15 exploration of chemical Kinetic of the bleaching reaction of RD40, 16 building a Visible Spectrophotometer, 17 fluorescence using homemade equipment, 18 finding the pK a values of thymol blue, 19 quantification of Allura Red in maraschino cherry juice, 20 construction of adsorption isotherms, 21 determination of glucose, 22 and quantification of Cu 2+ in solution. 23 Digital images acquired using smartphones, digital cameras, webcams, and desktop scanners were also used in academic research, and their uses can be found in recent reviews.…”
Section: ■ Introductionmentioning
confidence: 99%